Application of High-Flow Nasal Cannula in COVID-19: A Narrative Review - Cheng-Wei Liu; Shih-Lung Cheng (Life, 2022)
Background: During the first wave of COVID-19, the large influx of severely ill patients led to insufficient availability of beds in intensive care units and a shortage of ventilators. The shortage of ventilators, high mortality of intubated patients, and high risk of infections among healthcare workers involved in intubation were the main factors that led to the prevalence of noninvasive respiratory support during the pandemic. The high-flow nasal cannula (HFNC) is a commonly used, popular form of noninvasive respiratory support. Due to its unique physiological effects, HFNC can provide a high fraction of humidified oxygen and is satisfactorily comfortable for patients with COVID-19. However, before the COVID-19 era, there was little evidence on the application of HFNC in patients with acute respiratory failure caused by viral infection. Aim: This narrative review provides an overview of recent studies on the use of HFNC in patients with COVID-19-related acute hypoxemic respiratory failure. The main topics discussed include the probability of successful use of HFNC in these patients, whether late intubation increases mortality, the availability of convenient and accurate monitoring tools, comparison of HFNC with other types of noninvasive respiratory support, whether HFNC combined with the prone position is more clinically useful, and strategies to further reduce the infection risk associated with HFNC. The implication of this study is to identify some of the limitations and research gaps of the current literature and to give some advice for future research.